HUBUNGAN KEBIASAAN MEMBACA PUISI DENGAN KEMAMPUAN MENGIDENTIFIKASI UNSUR PEMBANGUN PUISI SISWA KELAS VIII SMPN 16 PONTIANAK - sari, yusnita; Mai Yuliastri Simarmata; Dini Hajjafiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is a relationship between the habit of reading poetry and the ability to identify the structural elements of poetry. The method used in this research is a quantitative method with a correlational research design. The population in this study consists of all eighth-grade students at SMPN 16 Pontianak, with a sample of 33 students from class VIII E. The data collection tools used in this research are two: a questionnaire to measure students' habits of reading poetry and a test to assess their ability to identify the structural elements of poetry. The results showed an rxy of 0.092, and the rtabel at a 5% significance level with N = 33 is 0.355. The data indicate that rxy < rtabel (0.092 < 0.355), which means we accept Ho and reject Ha. Therefore, it can be concluded that there is no relationship between the habit of reading poetry and the ability to identify the structural elements of poetry among eighth-grade students at SMPN 16 Pontianak.